LES ENTREPRISES FRANÇAISES FACE AUX OCCUPANTS (1940–1944): Entre collaboration, opportunisme et « nécessité de vivre ». Issue 2 (1st July 2019) - Durand, Sébastien
Abstract : Amid severe shortages of raw materials, labor, and transportation, companies in occupied France (1940–1944) sought alternative paths to what is commonly called "economic collaboration." They worked to find substitute supplies, convert to new product lines, alter their manufacturing methods, and even adapt to the black market. But few businesses could avoid the question of whether to provide goods and services to the occupier. The opportunities to do so were widespread, though they varied according to occupation, economic branch, and the passage of time during the Occupation. The German occupiers thus benefited from the French economy. With decisive help from the Vichy regime, the occupiers managed to force, induce, or entice French enterprises into their war economy—be they large industries formerly mobilized for French national defense, small and medium-sized firms, or agricultural producers.